The Influence of Online Shoe Purchasing After Onsite Trial Behavior - Nur Al Huda Ma’rifatullah; Astri Wulandari; Rahmat Hidayat (Journal of Governance, Taxation and Auditing, 2026)
This study examines how consumers’ experience of trying shoes in physical stores and their trust in online sellers influence online shoe purchase decisions. A descriptive quantitative design was applied, and data were collected through a survey involving 158 respondents in Bandung City. The respondents were determined through purposive sampling based on two main criteria: they had previously tried shoes in offline stores and had either purchased or considered purchasing shoes through e-commerce platforms. The collected data were processed using SPSS, covering instrument validity and reliability tests, classical assumption tests, multiple linear regression, partial and simultaneous hypothesis testing, and the coefficient of determination. The findings reveal that showrooming behavior significantly and positively affects online shoe purchase decisions. Online trust also shows a significant positive influence on consumers’ decisions to buy shoes through digital platforms. The simultaneous test further indicates that showrooming behavior and online trust jointly contribute to online purchase decisions, as reflected by an R Square value of 0.683. This means that 68.3% of the variation in online shoe purchase decisions can be explained by the two variables, while the remaining proportion is associated with other factors beyond the scope of this study. These results suggest that direct product evaluation in offline stores and consumer confidence in online sellers play a crucial role in shaping hybrid purchasing behavior in the digital marketplace.